MENINJAU ULANG ISTILAH BID’AH HASANAH SEBAGAI KONTRA WACANA TERHADAP BID’AH DHALALAH DI RUANG PUBLIK DAN AKADEMIK - Muhammad Lukman Arifianto Arifianto; Yusuf Hanafi; Faris Khoirul Anam (Jurnal Masyarakat dan Budaya, 2021)
Abstract: This paper is aimed to revisit the existence terminology of Bid’ah Hasanah (Good Innovation) in the public and academic sphere as a counter discourse against the dominance of established meaning of Bid’ah which in terms of Islamic Sharia is interpreted as an act of misguidance (Bid’ah Dalalah). Counter discourse is a way of thinking that opposes an institutionalized discourse. In this context, we try to investigate the emergence of this term and describe how it is expressed as an opposing thought against the negative meaning of Bid'ah which was discursively long-established in the public and academic sphere by conducting the grounded approach. The data collected is taken from a mini survey and some specific discourses related to this topic such as the discussions in some chapters of the Islamic teaching textbook, and discourses from the online sources including social media and some websites affiliated with certain religious groups. The result shows that the terminology of Bid’ah Hasanah is emerged and echoed by traditional religious groups to label the non-exclusive worships (Ghairu Mahdhah) that originally don’t require any special rules in its implementation. According to them, this term is retrieved and interpreted from several Hadiths and the words of the Prophet’s companions. In the public and academic sphere, this term is still being roughly debated by some religious groups, mainly the Salafis and the traditionals, due to their differences in the methodology of meaning to this term. The Salafis prioritize the textual rigorous Sharia meaning contained in this term, whereas traditional parties put forward the literal and original meaning in understanding this term.